Comparative Genomic Analysis Reveals Extensive Genetic Variations of WRKYs in Solanaceae and Functional Variations of CaWRKYs in Pepper - Cheng, Yuan; Ahammed, Golam Jalal; Yao, Zhuping; Ye, Qingjing; Ruan, Meiying; Wang, Rongqing; Li, Zhimiao; Zhou, Guozhi; Wan, Hongjian (Frontiers in Genetics, 2019)
As a conserved protein family, WRKY has been shown to be involved in multiple biological processes in plants. However, the mechanism of functional diversity for WRKYs has not been well elucidated. Here, totally 223 solanaceae WRKY members from pepper, tomato and potato, were analyzed using comparative genomics. A tremendous genetic variation among WRKY members of different solanaceous plants or groups was demonstrated by the variations of WRKY number/size, group constitution, phylogenetic relationship, gene structure, and domain composition. Except for the extensive genetic variations, certain degree of conservatism for solanaceae WRKYs was also revealed. The phylogenetic analysis showed that except for the known WRKY groups (I, IIa/b/c/d/e and III), two extra WRKY subgroups specifically existed in solanaceous plants, which were named as group IIf and group IIg for the convenience of group-wise analysis in this study. Moreover, the variant zinc-finger structure (CX4,7CX22-24HXC) in group III of solanaceae WRKYs was identified. Expression profile of CaWRKY genes suggested their potential roles in pepper development and stress responses, and demonstrated a functional division pattern for pepper CaWRKYs. Furthermore, functional analysis using Virus Induced Gene Silencing (VIGS) revealed critical roles of two CaWRKYs (CaWRKY45 and CaWRKY58) in plant response to disease and drought, respectively. This study provides a solid foundation for further dissection of the evolutionary and functional diversity of solanaceae WRKYs in crop plants.